Phylogenetic analysis and genetic diversity of Phytophthora palmivora causing black pod disease of cocoa in Malaysia - Alsultan, Wael; Vadamalai, Ganesan; Mohd Saud, Halimi; Ahmad, Khairulmazmi; Wong, Mui Yun; Mohd Jaaffar, Ahmad Kamil; Al-Sadi, Abdullah M.; Rashed, Osamah; Nasehi, Abbas (American Phytopathological Society, 2021)
Black pod, caused by Phytophthora spp., occurs worldwide and is a major problem for cocoa farmers in Malaysia. Limited studies addressed causal agents of black pod disease of cocoa in Malaysia as well as their genetic diversity. Therefore, this study was initiated to isolate and identify Phytophthora from the main cocoa plantations infected by black pod in Malaysia using sequence analyses of the ITS rDNA, EF-1α, and COX1 gene regions. A total of 36 Phytophthora isolates were obtained from infected cocoa plantations from five states of Malaysia in 2016 and 14 isolates in 2013. Six Phytophthora isolates obtained from the durian crop, “the king of fruit”, in 2013 were also used in this study. Results of phylogenetic analyses of the combined dataset of the ITS rDNA, COX1, and EF-1α confirmed that all Phytophthora isolates belonged to P. palmivora. P. palmivora isolates obtained from cocoa and durian clustered into different subclades based on the three regions examined. The study also examined the genetic diversity within a population of 56 P. palmivora isolates using random amplified polymorphic DNA (RAPD) and intersimple sequence repeat (ISSR) markers. The results of both markers indicated relatively high diversity among P. palmivora isolates. The complete separation was based on host and year of isolation. The study suggests that one species of Phytophthora, namely, P. palmivora, is responsible for black pod of cocoa in Malaysia. However, the relatively high genetic diversity and separation of isolates into different clades may suggest that P. palmivora has been introduced into Malaysia via different sources.